Travelling Fellowship Program for Football Medicine; Report on an Experience - Seifbarghi, Tohid (Tehran University of Medical Sciences, 2012)
Football medicine has developed in the world in recent years. AFC Medical Committee, established the idea of football medicine travelling fellowship two years ago and provided high-level healthcare services to football players in Asian countries. This is a report on my one month experience in a travelling fellowship program for football medicine which is attempting to tell the reader about the interesting event that I experienced. This course has been held between Jan 15 to Feb 10, 2012 in 3 Asian countries: Qatar, Thailand and Malysia. The experience provided me with the valuable suggestions for future travelling fellowship periods.